Beyond the Vampire: Revamping Thai Monsters for the Urban Age - Katarzyna Ancuta (My University, 2017)
This article revisits two of the most iconic Thai monstrosities, phi pop and phi krasue, whose changing representation owes equally as much to local folklore, as to their ongoing reinterpretations in popular culture texts, particularly in film and television. The paper discusses two such considerations, Paul Spurrier’s P (2005) and Yuthlert Sippapak’s Krasue Valentine (2006), films that reject the long-standing notion that animistic creatures belong in the countryside and portray phi pop and phi krasue’s adaptation to city life. Though commonplace, animistic beliefs and practices have been deemed incompatible with the dominant discourses of modernization and urbanization that characterise twenty-first century Thailand. Creatures like phi pop and phi krasue have been branded as uncivilised superstition and ridiculed through their unflattering portrayals in oddball comedies. This article argues that by inviting these monsters to relocate to contemporary Bangkok, Spurrier and Sippapak redefine their attributes for the modern urban setting and create hybrids by blending local beliefs and cinematic conventions. The creatures’ predatory character is additionally augmented by the portrayal of the city as itself vampiric. The article therefore reads these predatory spirits in parallel with the metaphor of the female vampire – a sexually aggressive voracious creature that threatens male patriarchal order and redefines motherhood.
Keywords: Vampire; Creatures; Popular culture; Superstition; Representation; Jungle; Southeast Asian Sociopolitical Studies